The Training Needs of Teachers in the Light of Technology-Based Education from the Point View of Lower Elementary Schools’ Principals in Hebron Governorate - Abu Minshar, Manal Majed; Nawajah, AbdAlrahman Mohammad (Journal of Educational and Psychological Sciences, 2022)
This study aimed to know some of the teachers’ training needs in light of Technology-Based Education from the Point View of Lower Elementary Schools’ Principals in Hebron Governorate. The researchers used the descriptive analytical approach. The study population consisted of (69) principals of the lower basic stage schools. The questionnaire was designed to collect information and consisted of 37 statements which were divided into five dimensions. The results of the study showed that the proposed training needs for teachers in light of the integration of technology from the point of view of the principals was at a high degree. The mean was (3.85) with (%76.8) percentage. The need was ranked from the most to the least importance as following: Training needs that related to planning for the teaching subject, with an average of )3.94) and a percentage of (%78.8), training needs related to the methods of implementing the lesson, with an average of (3.91) and a percentage of (%78.2), training needs related to evaluating students’ performance with an average of (3.86) and a percentage of (%77.3), training needs related to controlling the educational situation with a mean of (3.84) and a percentage of (%76.5) training needs related to digital educational resources with an average of (3.67) and a percentage of (%73.4). The study also showed that there are no statistically significant differences at the level (α≤0.05) in the average responses of the study sample due to the gender, educational qualification, and years-of-experience variables. The main recommendation was to modify the curriculum and educational content to suit the skills of integrating technology, so that the teacher can achieve the goals effectively and efficiently.